The Beneficial Effects of Ranolazine on Cardiac Function After Myocardial Infarction Are Greater in Diabetic Than in Nondiabetic Rats. (September 2014) - Mourouzis, Iordanis; Mantzouratou, Polixeni; Galanopoulos, Georgios; Kostakou, Erietta; Dhalla, Arvinder K.; Belardinelli, Luiz; Pantos, Constantinos
Ranolazine (RAN) is known to exert both anti-ischemic and antidiabetic actions. Thus, this study has explored the hypothesis that RAN would have greater effect on the recovery of cardiac function in diabetic mellitus (DM) rat hearts following myocardial infarction (MI). Myocardial infarction was induced in nondiabetic (MI, n = 14) and diabetic (streptozotocin induced; DM-MI, n = 13) Wistar rats by permanent ligation of the left coronary artery. Cardiac function was evaluated using echocardiography (left ventricular ejection fraction %) and in isolated heart preparations by measuring left ventricular developed pressure (LVDP), and the positive and negative first derivative of LVDP (±dp/dt). Ranolazine (20 mg/kg, ip once a day) was administered 24 hours after surgical procedure for 4 weeks to nondiabetic (MI + RAN, n = 17) and diabetic rats (DM-MI + RAN, n = 15). The RAN improved the recovery of function in both the nondiabetic and the diabetic postinfarcted hearts but this effect was greater and achieved statistical significance only in the diabetic group. The RAN resulted in increased levels of phosphorylated protein kinase B (Akt) and mammalian target of rapamycin (mTOR, a component of Akt signaling) in both nondiabetic and diabetic infarcted hearts without changes in the activation of mitogen-activated protein kinases (MAPKs; p38 MAPK, c-Jun N-terminal kinase, and extracellular signal-regulated kinase). In addition, in diabetic hearts, RAN resulted in a significant increase in the ratio of sarcoplasmic Ca 2+ -ATPase/phospholamban (a target of Akt signaling, 2.0-fold increase) and increased levels of phosphorylated calcium-regulated adenosine monophosphate-activated protein kinase (AMPK; 2.0-fold increase). In diabetic animals, RAN increased insulin and lowered glucose levels in serum. In conclusion, the beneficial effect of RAN on the recovery of cardiac function after MI was greater in DM rats. This response was associated with activation of Akt/mTOR and AMPK. These findings provide a plausible explanation for the results of the Type 2 Diabetes Evaluation of Ranolazine in Subjects With Chronic Stable Angina (TERISA) trial, which showed a greater antianginal effect of RAN in patients with coronary artery disease and diabetes.